1998
DOI: 10.1046/j.1365-2044.1998.435-az0528.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical face masks and downward dispersal of bacteria

Abstract: SummaryThe ability of face masks to prevent forward dispersal of bacteria is offset by the possibility that they may increase vertical shedding of bacteria from the face during facial movement. To investigate this, a blood agar plate was placed 30 cm directly below the lips of 20 volunteers who were encouraged to talk for 20 min while moving their heads from side to side, without a face mask for the first 5 min and then with a standard, soft pleated face mask for the subsequent 15 min. The agar plates were cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 10 publications
(10 reference statements)
1
38
0
Order By: Relevance
“…It is assumed that this may be caused by the higher risk of iatrogenic infection due to oral flora during office-based procedures compared to those performed under sterile conditions of the operating room [10]. Previous studies on the effect on agar plate contamination revealed a significant increase in colony counts, with a predominance of streptococci, when not wearing a face mask and talking [18-20]. In this retrospective study we did not have the opportunity to evaluate for “no-talking” policy during the anti-VEGF injection which caused the endophthalmitis.…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed that this may be caused by the higher risk of iatrogenic infection due to oral flora during office-based procedures compared to those performed under sterile conditions of the operating room [10]. Previous studies on the effect on agar plate contamination revealed a significant increase in colony counts, with a predominance of streptococci, when not wearing a face mask and talking [18-20]. In this retrospective study we did not have the opportunity to evaluate for “no-talking” policy during the anti-VEGF injection which caused the endophthalmitis.…”
Section: Discussionmentioning
confidence: 99%
“…In a collaborative intensive care unit (ICU) study, a set of five different preventive interventions including full barrier precautions was successfully implemented, but the study did not evaluate the relative importance of each of the individual interventions separately [15]. In another study, the use of surgical face masks reduced bacterial contamination of the area in front of the operator's face [16], who, however, was asked to talk during the 20-min observation period and to turn his/her head 90°every 30 s [16]. The use of precautions such as masks and gowns should not be considered as an excuse to relax on general hygienic and sterile conditions.…”
Section: Nursing Carementioning
confidence: 99%
“…It is not difficult to demonstrate the obvious ability of face masks to diminish the dispersion of bacteria from the mouth and nose. 73 Talking adds to dispersion, but remaining silent can appear inhumane during spinal insertion. In a study deliberately designed to address the question of mask-wearing for spinal insertion, Philips et al found that a fresh face mask virtually abolished bacterial contamination of a culture plate placed at a horizontal distance of 30 cm from the mouth.…”
Section: Preventive Measuresmentioning
confidence: 99%